2002
DOI: 10.1177/073724770202800103
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Assessment Scores and Life Outcomes for Students with Significant Disabilities: Are They Related?

Abstract: This study investigated the extent to which alternate assessment scores for 12th-grade students in Kentucky's Alternate Portfolio Program for students with significant disabilities correlated with a measure of post-school outcomes for these students approximately one year after completing school. Forty-one former students participated in the study and in a comprehensive interview with their families. Life outcomes were measured through an author-developed tool, the Life Dimensions Scoring Rubric. No significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In addition, lack of communication supports in these classrooms was worrisome, as communication has been linked to positive post-school outcomes (Kleinert et al, 2002). Specifically, students with CCN in the present analysis interacted with teachers less often and were more likely to be engaged in a passive task than other students with SCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lack of communication supports in these classrooms was worrisome, as communication has been linked to positive post-school outcomes (Kleinert et al, 2002). Specifically, students with CCN in the present analysis interacted with teachers less often and were more likely to be engaged in a passive task than other students with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lack of communication supports in these classrooms was worrisome, as communication has been linked to positive post-school outcomes (Kleinert et al, 2002).…”
Section: Ecobehavioral Characteristics Of Self-contained High School mentioning
confidence: 99%
“…Results such as these raise concerns regarding whether AAS leads to greater or lesser access to general education curriculum (Ryndak et al, 2014) and whether it sufficiently impacts quality of life outcomes (Kleinert et al, 2002). Our findings may indicate even greater concerns regarding the AAS for promoting CCR.…”
Section: Operationalizing Ccr Within Common Core and Alternate Standardsmentioning
confidence: 68%
“…But, they found no correlation with the quality of IEP objectives. Kleinert, Garrett, et al (2002) found no relationship between alternate assessment scores and a measure of postschool outcomes for Kentucky students, but this was confounded by the fact that most students in their sample had poor outcomes. Tindal et al (2003) developed a series of standardized tasks that could be considered as related to the same construct defined in a largescale assessment program in an effort to evaluate technical adequacy (i.e., reliability and construct validity).…”
Section: Is Alternate Assessment Influencing Policy O N School Reform?mentioning
confidence: 84%
“…Kleinert et al (1997) proposed that "one of the keys to ensuring high expectations for every child is requiring that all students be included in measures of educational accountability" (p. 88). Kentucky was the first state to realize that "all means all" and to identify a way to include students with the most significant disabilities in its accountabil- Kleinert, Garrett, et al (2002) Relationship between AA scores and postschool outcomes…”
Section: P R O M I S E S O F a L T E R N A T E A S S E S S M E N Tmentioning
confidence: 99%